1992
DOI: 10.1007/bf02270814
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Botshol (The Netherlands) by reduction of external nutrient load: Recovery of the Characean community

Abstract: The formerly rich characean community in Botshol with six species, of which the rare Nitellopsis obtusa and Chara hispida dominated at many sites, decreased to only two species, Chara globularis and C. connivens, in the period 1980-1988. The macrophyte Najas marina also remained at some sites, and the aquatic moss Fontinalis antipyretica and the filamentous alga Vaucheria dichotoma predominated at many sites. These phenomena may have been due to eutrophication by the inlet of polluted water. This process of eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Submerged macrophytes play a very important role in stabilising the clear-water state in shallow mesotrophic and eutrophic lakes (Perrow et al, 1997;Scheffer, 1998). Because charophytes are able to colonise lakes rapidly (Simons et al, 1994;Beltman & Allegrini, 1997;Meijer et al, 1999), they often play an important role in early stages of recovery after reduction of high anthropogenic nutrient inputs (Simons et al, 1994;Van den Berg, 1999). There is much evidence that charophytes have a particularly strong positive effect on water transparency (Crawford, 1979;Scheffer et al, 1994;Van den Berg et al, 1998;Van Donk & Van de Bund, 2003. Responses of macrophytes, phytoplankton, zooplankton and other important food-web constituents to combinations of nutrient addition and the abundance of zooplanktivorous fish were tested in in situ enclosures in a shallow lake dominated by charophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Submerged macrophytes play a very important role in stabilising the clear-water state in shallow mesotrophic and eutrophic lakes (Perrow et al, 1997;Scheffer, 1998). Because charophytes are able to colonise lakes rapidly (Simons et al, 1994;Beltman & Allegrini, 1997;Meijer et al, 1999), they often play an important role in early stages of recovery after reduction of high anthropogenic nutrient inputs (Simons et al, 1994;Van den Berg, 1999). There is much evidence that charophytes have a particularly strong positive effect on water transparency (Crawford, 1979;Scheffer et al, 1994;Van den Berg et al, 1998;Van Donk & Van de Bund, 2003. Responses of macrophytes, phytoplankton, zooplankton and other important food-web constituents to combinations of nutrient addition and the abundance of zooplanktivorous fish were tested in in situ enclosures in a shallow lake dominated by charophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Hosper 1997;Scheffer 1998), an increase in the phosphate concentration can lead to a rise in the phytoplankton levels and a decrease of the light penetration in the water, which is probably the primary controlling factor for the germination and growth of Charophyta (Blindow 1988;Simons et al 1992). The studies described in this article show that pumping suppletion water with a different chemical composition into a nature reserve in periods of drought can have an internal eutrophication effect.…”
Section: Methodsmentioning
confidence: 85%
“…These measures included an iron-chloride dosing plant in the supply route and the isolation from the agricultural areas by dams to prevent runoff. In 1990 the Chara communities did recover (Simons et al 1992), but after 1992 the Chara community collapsed and a undulating pattern was established of collapsing and recovering Chara communities and submerged macrophytes and P levels fluctuated below and above the threshold level of 0.02 mg P l À1 (Rip et al 1994).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Substantial reduction of nutrient loading can be useful, particularly in cases when nutrients come from point sources (Simons et al 1994;Moss et al 1996a;Jeppesen et al 2005Jeppesen et al , 2007Søndergaard et al 2005a), but it might not produce the desired effect or such an effect can be considerably delayed in cases of accumulation of phosphorus in the sediment or diffuse external nutrient sources (Lauridsen et al 2003;Carpenter 2005;Søndergaard et al 2007) A number of studies have demonstrated, however, that sizeable reduction in fish densities shifts lakes and ponds from phytoplankton to submerged vegetation dominance, thus improving the water quality and reducing the risk of cyanobacterial bloom occurrence (Shapiro and Wright 1984;Shapiro 1990Shapiro , 1995Gulati and van Donk 2002;Søndergaard et al 2007;Van Wichelen et al 2007). Removal of all or most of the fish or addition of piscivores with the aim of reducing phytoplankton biomass is referred to as biomanipulation (Shapiro and Wright 1984;Moss et al 1996a).…”
Section: Introductionmentioning
confidence: 99%